Incorporating Values of Moderate Islam for the 21st Century Learners in an English as a Foreign Language Class - Fachri Ali (Edukasia Islamika, 2018)
This present study explores how to incorporate values of moderate Islam for the 21st century learners in an English as a Foreign Language (EFL) class. It was conducted in the single class consisting of 44 undergraduate students who took English for Islamic Education course at Institut Agama Islam Negeri Pekalongan, Indonesia. The data were collected through observation and interview. The finding exposes that five values of moderate Islam could be noticed in the EFL class, namely: objectivity, tolerance in encountering diversity, inclusiveness in receiving current issues, logic and flexibility in understanding texts, and innovation in daily life. Another result demonstrates the lecturer’s pivotal roles in incorporating the values of moderate Islamic for the 21st century learners in the classroom setting. The roles included facilitating as a good model to incorporate the values, such as respecting diversity without any discrimination of gender and social backgrounds and having enthusiasm for helping the learners, organizing an online group on Edmodo learning management system, and providing the EFL learners with opportunities to foster good morality in both individual and group learning activities. The study also promotes that relating to the use of learning materials, online news articles containing Islamic values were used as the authentic materials, and EFL teaching may impact on the learners’ disappointment or conflict with the culture embedded in the learning materials.